Factors of the Development of Ukraine’s Digital Economy: Identification and Evaluation - Vasyltsiv, T.; Mulska, O.; Levytska, O.; Lupak, R.; Semak, B.; Shtets, T. (Science and Innovation, 2024)
Introduction. Digital transformation (hereinafter referred to as digitalization) and the widespread introduction of digital technologies in all spheres of public life and economic relations are key milestones in the development of the world economy. Problem Statement. The economy digitalization requires effective government regulation and support, the mechanisms and tools of which shall be developed in accordance with the current conditions of the digitalization environment through identifying appropriate incentives. Purpose. The purpose of this research is the identification of factors and the assessment of the development of Ukraine’s digital economy based on the methodological approach proposed by the authors. Materials and Methods. The methodology for assessing the factors of the development of the digital economy (based on the calculation of the integrated index and the results of the expert survey) involves the use of the main components method and the multiplicative approach. The evaluation methodology comprises the six components: (1) strategy, (2) design, (3) expertise, (4) qualitative evaluation, (5) quantitative evaluation, and (6) conclusion. The factors of digital economy development are grouped based on the following elements: (1) selfsufficiency, (2) efficiency, (3) involvement, (4) infrastructure, (5) readiness, and (6) cooperation. Results. The spheres to which the government policy in the sphere of digital economy development of Ukraine is directed have been defined. The integrated index is equal to 0.603 that which is an evidence of the medium level of development (favorable status) of the digital technology environment. The highest values of the index have reported for self-sufficiency (0.884), efficiency (0.717), and readiness (0.753). The lowest index has been obtained for the involvement component (0.224). Conclusions. Favorable environment for the economy digitalization can be achieved through the implementation of measures to develop appropriate infrastructure and organizational and institutional support for pursuing policies of digitalization of the economic system and society, as well as projects and programs for digital cooperation.